Internally generated intangible assets the vaccine for UK listed finance industry financial contagion? - Louw, Gerhard (College of Accounting, 2025)
Context: Internally generated non-capitalised intangible assets (IGNIAs) are not included in companies' balance sheets per international accounting standards, as they do not contribute to providing firms with resilience during crises. However, some companies gain a competitive advantage by continuously investing in IGNIAs , which management and investors should prioritize to foster resilience during unforeseen crises. Purpose: This study aims to determine whether investment in IGNIAs provided resilience, proxied by Return on Assets (ROA), during the COVID-19 crisis for 257 UK- listed finance firms from 2016-2023. The focus is on the UK finance industry due to its significant role in global financial contagion during crises. Research Design: This study used quantitative methods, employing firm-specific variables to test the hypotheses developed from existing theories. A longitudinal design was used with cross-sectional data from various firms in the finance industry. The study reviewed the relationship between UK finance firms' investment in IGNIAs and their resilience. It compared the resilience of firms that invested more in IGNIAs before the COVID-19 crisis to those that invested less, to determine if these assets contributed to their resilience. Main Findings: The study did not find a statistically significant relationship between investment in IGNIAs and resilience measured by ROA for the entire sample of 257 UK finance firms from 2016-2023. However, a somewhat statistically significant relationship was found between IGNIAs and resilience in the financial services industry only after the COVID-19 pandemic period, 2020-2023. Contribution: This study provides insights into the importance of IGNIAs in fostering resilience, especially for the finance industry, and contributes to the ongoing debate on whether these intangible assets should be included in firms' balance sheets. It highlights the need for industry-specific measures to resolve the contentious issue of capitalising IGNIAs.Recommendations and Implications: Management should prioritise continuous investment in IGNIAs to foster resilience and provide protection against unforeseen market crises. Standard-setting bodies should reconsider disclosing IGNIAs, as they are important factors for investors to consider when making informed investment decisions.